REGULATION OF EXPORT ACTIVITIES OF SMALL BUSINESS IN THE REPUBLIC OF UZBEKISTAN - Rakhmatjanov Lazizkhon Turabaevich; Khabibullaev Davronbek Bakhodir ugli (Scholar Express Journals, 2023)
In this article are discussed the innovativeness of small business, the need to clearly define the size of a small and medium-sized business as a recipient of support in export activities..
Keywords: small medium-sized business; export activities; support